Maximizing in vivo target clearance by design of pH-dependent target binding antibodies with altered affinity to FcRn. Issue 7 (3rd October 2017) - Yang, Danlin; Giragossian, Craig; Castellano, Steven; Lasaro, Marcio; Xiao, Haiguang; Saraf, Himanshu; Hess Kenny, Cynthia; Rybina, Irina; Huang, Zhong-Fu; Ahlberg, Jennifer; Bigwarfe, Tammy; Myzithras, Maria; et al.
ABSTRACT: Antibodies with pH-dependent binding to both target antigens and neonatal Fc receptor (FcRn) provide an alternative tool to conventional neutralizing antibodies, particularly for therapies where reduction in antigen level is challenging due to high target burden. However, the requirements for optimal binding kinetic framework and extent of pH dependence for these antibodies to maximize target clearance from circulation are not well understood. We have identified a series of naturally-occurring high affinity antibodies with pH-dependent target binding properties. By in vivo studies in cynomolgus monkeys, we show that pH-dependent binding to the target alone is not sufficient for effective target removal from circulation, but requires Fc mutations that increase antibody binding to FcRn. Affinity-enhanced pH-dependent FcRn binding that is double-digit nM at pH 7.4 and single-digit nM at pH 6 achieved maximal target reduction when combined with similar target binding affinities in reverse pH directions. Sustained target clearance below the baseline level was achieved 3 weeks after single-dose administration at 1.5 mg/kg. Using the experimentally derived mechanistic model, we demonstrate the essential kinetic interplay between target turnover and antibody pH-dependent binding during the FcRn recycling, and identify the key components for achieving maximal target clearance. These results bridge the demand for improved patient dosing convenience with the "know-how" of therapeutic modality by design.